CULINARY TOURISM DEVELOPMENT STRATEGY TO INCREASE TOURISM ATTRACTIVENESS: A LITERATURE REVIEW - Komang Shanty Muni Parwati; Firman Sinaga, Mohamad Tamrin (Adisam Publisher, 2025)
This study explores strategies that can be applied in the development of culinary tourism to increase the tourism appeal of a destination. Culinary tourism is an important component in the tourism industry, which not only adds value to the tourist experience but also has the potential to become a major attraction that differentiates a destination from others. Through a literature review, this study identified several key strategies, including strengthening local culinary branding, organizing culinary festivals and events, developing special culinary infrastructure and areas, and effective digital promotion. In addition, innovation in preserving traditional culinary and collaboration between sectors are also recognized as key elements in increasing the appeal of culinary tourism. The results of this study indicate that the implementation of these strategies can increase the number of tourist visits, strengthen local cultural identity, and support regional economic growth. These findings are expected to provide guidance for policy makers and industry players in designing holistic and sustainable culinary tourism development programs.